Simvastatin-induced endothelial cell detachment and microparticle release are prenylation dependent - Diamant, Michaela; Tushuizen, Maarten E.; Abid-Hussein, Mohammed N.; Hau, Chi M.; Böing, Anita N.; Sturk, Augueste; Nieuwland, Rienk (Thrombosis and Haemostasis, 2008)
Statins reduce cardiovascular disease risk and affect endothelial function by cholesterol-dependent and independent mechanisms. Recently, circulating (detached) endothelial cells and endothelial microparticles (EMP) have been associated with endothelial functioning in vitro and in vivo.We investigated whether simvastatin affects endothelial detachment and release of EMP. Human umbilical vein endothelial cells (HUVECs) were incubated with clinically relevant concentrations of simvastatin (1.0 and 5.0 µM), with or without mevalonic acid (100 µM) or gera-nylgeranylpyrophosphate (GGPP; 20 µM) for 24 hours, and analyzed by flowcytometry andWe stern blot. Simvastatin at 1.0 and 5.0 µM increased cell detachment from 12.5 ± 4.1% to 26.0 ± 7.6% (p=0.013) and 28.9 ± 2.2% (p=0.002) as well as EMP release (p=0.098 and p=0.041, respectively).The majority of detached cells was apoptotic, although the fraction of detached cells that showed signs of apoptosis (>70%) was unaffected by simvastatin. Detached cells and EMP contained caspase 3 and caspase 8,but not caspase 9. Restoring either cholesterol biosynthesis and prenylation (mevalonate) or prenylation alone (GGPP) reversed all simvastatin-induced effects on cell detachment and EMP release. Adherent cells showed no signs of simvastatin-induced apoptosis. Simvastatin promotes detachment and EMP release by inhibiting prenylation, presumably via a caspase 8-dependent mechanism. We hypothesize that by facilitating detachment and EMP release, statins improve the overall condition of the remaining vascular endothelium.
Keywords: Anoikis; apoptosis; cardiovascular disease; endothelium; micro-particles; statins